Selling Syringes to injecting drug users: A study of five pharmacies in Hanoi, Vietnam - Christopher A. Pankonin,1 Peter Higgs,2 Gary Reid,2 Campbell Aitken.3 (The Journal of Infection in Developing Countries, 2008)
Background: HIV continues to spread rapidly throughout Vietnam with injection drug use remaining the main risk factor for infection. The extent of pharmacy-based needle and syringe distribution has not previously been measured in Vietnam; this article reports on a pilot study exploring pharmacy-based harm reduction activities in Vietnam's capital, Hanoi.Methodology: Five pharmacies located in Dong Da and Thanh Xuan districts in Hanoi, where two peer-based needle and syringe programs (NSPs) also operate, recorded the numbers of syringes sold to injecting drug users (IDUs) over a one-week period. Each pharmacist participated in a semi-structured interview aimed at understanding the pharmacists' views of syringe distribution and HIV prevention.Results: The five pharmacies sold an average of 93 syringes per pharmacy to IDUs during the study week. Pharmacists demonstrated a solid understanding of HIV transmission risk factors and a strong commitment to continuing HIV prevention activities.Conclusions: Our data are based on few observations and are very preliminary, but suggest that pharmacies contribute a significant proportion of the total syringe supply to IDUs in Hanoi. Given adequate support, pharmacies could be an effective vehicle for scaling up harm reduction services in Hanoi and throughout Vietnam.